2021
DOI: 10.26803/ijlter.20.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Habits of Mind in the Inculcation of Self-Directed Learning Skills in Pre-Service Teachers

Abstract: The purpose of this research was to determine the extent to which pre-service teachers were self-directed before implementing habits of mind as a teaching strategy. The researchers purposively focused on first to fourth-year BEd students. The sample consisted of 277 students who volunteered. A concurrent mixed-method triangulation approach was applied. Even though the students overestimated themselves in Williamson's self-rating scale of self-directed learning, the habits of mind positively affected developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The selection of the mind mapping technique combined with the CPL learning model is a collaboration that is very appropriate and suitable in increasing interest learn students' thinking habits (Klassen, 2006;Ng & Ng, 2015). Students with a high interest in learning will have high creative thinking skills which is one of the indicators of habits of mind making it easier to achieve learning goals (Van Tonder et al, 2021). Mind mapping is very effectively used to bring up the hidden ideas that students have, mind mapping is ideal for jumping up students' thinking through forming, visualizing, designing, taking notes, solving problems, making decisions, revising and clarifying main topics so that students can complete assignments even though there are many (Sulfemi, 2019), besides that based on several studies that have been carried out the mind mapping technique has also been shown to increase understanding, creativity, and increase self-regulation of students which includes indicators of habits of mind (Putro et al, 2021).…”
Section: Results Of Student Mind Mapping On the Concept Of Biodiversitymentioning
confidence: 99%
“…The selection of the mind mapping technique combined with the CPL learning model is a collaboration that is very appropriate and suitable in increasing interest learn students' thinking habits (Klassen, 2006;Ng & Ng, 2015). Students with a high interest in learning will have high creative thinking skills which is one of the indicators of habits of mind making it easier to achieve learning goals (Van Tonder et al, 2021). Mind mapping is very effectively used to bring up the hidden ideas that students have, mind mapping is ideal for jumping up students' thinking through forming, visualizing, designing, taking notes, solving problems, making decisions, revising and clarifying main topics so that students can complete assignments even though there are many (Sulfemi, 2019), besides that based on several studies that have been carried out the mind mapping technique has also been shown to increase understanding, creativity, and increase self-regulation of students which includes indicators of habits of mind (Putro et al, 2021).…”
Section: Results Of Student Mind Mapping On the Concept Of Biodiversitymentioning
confidence: 99%
“…SDL is characterised by individuals' inherent predisposition towards this particular learning mode and their ability to autonomously engage in the learning process. SDL is an educational approach wherein learners take responsibility for their own learning process (Van Tonder et al. , 2021).…”
Section: Mentoringmentioning
confidence: 99%
“…SDL is characterised by individuals' inherent predisposition towards this particular learning mode and their ability to autonomously engage in the learning process. SDL is an educational approach wherein learners take responsibility for their own learning process (Van Tonder et al, 2021). Knowles (1975) is well-known for his definition of SDL as a process in which individuals take the initiative, with or without the support of others, to identify their learning needs, formulate learning goals, identify human and material resources for learning, select and implement appropriate learning strategies, and assess learning outcomes (p. 18).…”
Section: Self-directed Learningmentioning
confidence: 99%
“…The education system needs to go beyond teaching basic skills and focus on developing critical thinking and self-directed learning (SDL) skills in students. This is important to address global issues, for example, individuals who can merely read, write, and count, and prepare students for the demands of the job market (Van Tonder et al, 2021). Teachers should act as facilitators and create a student-centred learning environment to promote self-directed learning.…”
Section: Introductionmentioning
confidence: 99%